Notes and recommendations for the establishment of control programs for taeniasis and cysticercosis due to Taenia solium in Peru - Héctor H. García; Armando E. González; Seth E. O’Neal; Robert H. Gilman (Revista Peruana de Medicina Experimental y Salud Pública, 2018)
Neurocysticercosis is a nervous system infection caused by the larvae (cysticercus) of the pork tapeworm (Taenia solium). Neurocysticercosis is the primary cause of acquired epilepsy worldwide and, therefore, a global public health problem. On the other hand, T. solium taeniasis/cysticercosis is one of very few infectious diseases considered to be potentially eradicable. Recently, a large-scale elimination program in Tumbes, Peru, demonstrated the feasibility of interrupting transmission. Based on these advances, a series of initial guidelines are proposed aimed at setting out the foundations for regional and national taeniasis/cysticercosis control programs, with simple and feasible local interventions as a starting point.